Obesity Hypoventilation Syndrome (Pickwickian Syndrome): A Literature Review - Betcy, Betcy; Prasenohadi, Prasenohadi; Ramadhan, Alfin Ridha; Aurora, Ruth Grace; Alatas, Mohamad Fahmi (Respiratory Science, 2024)
Obesity hypoventilation syndrome (OHS), also known as Pickwickian syndrome, is a respiratory disorder characterized by reduced alveolar ventilation and elevated daytime carbon dioxide levels, primarily associated with obesity. If untreated, OHS can progress to pulmonary hypertension (PH) and ultimately heart failure. The exact prevalence of OHS in the general population remains unclear, but studies estimate it to range from 8% to 12.3%, increasing with obesity prevalence. This review discusses the diagnostic criteria for OHS, the utility of the STOP-Bang questionnaire in screening, and advances in understanding the pathophysiology and management of OHS, focusing on heart failure with preserved ejection fraction (HFpEF). Accurate diagnosis of OHS is critical and requires a thorough approach involving an extensive patient medical history and physical examination to differentiate OHS from obstructive sleep apnea (OSA). Key diagnostic tests include serum bicarbonate levels and arterial blood gas (ABG) analysis, to confirm the hypercapnia and identify the severity of hypoventilation. Given the rising prevalence of obesity worldwide and the serious complications associated with untreated OHS, early and accurate identification of OHS is essential, as it can prevent the progression to severe pulmonary hypertension (PH) and the subsequent development of heart failure (HF).